Acute Promyelocytic Leukemia Presenting With a Myeloid Sarcoma of the Spine: A Case Report and Literature Review - Shu, Xuemei; Wu, Qiuling; Guo, Tao; Yin, Hua; Liu, Jingdi (Frontiers in Oncology, 2022)
Myeloid sarcoma is a rare extramedullary tumor of immature myeloid cells. Certain known acute myeloid leukemia cytogenetic abnormalities, in particular t(8,21), has been associated with a higher incidence. Myeloid sarcoma, rarely happened in acute promyelocytic leukemias, is more common in recurrent patients after the advent of all-trans retinoic acid (ATRA), were rare in untreated acute promyelocytic leukemia. We describe a case, to our knowledge, of de novo myeloid sarcoma of the spine confirmed as acute promyelocytic leukemia. Myeloid sarcoma is diagnosed by spinal tumor biopsy, and microscopic examination of a bone marrow smear and cytogenetic analysis led to a confirmed diagnosis of acute promyelocytic leukemia.